PENGEMBANGAN BAHAN AJAR BERBASIS BUKU CERITA TENTANG EKOSISTEM DALAM MENUMBUHKAN KARAKTER PROFIL PELAJAR PANCASILA DI SMA NEGERI 2 TILAMUTA - Tudja, Rahmawaty; Nusantari, Elya; Sidik Katili, Abubakar; Wahyuni K. Baderan, Dewi; Nur Akbar Abay, Moh. (Jurnal Biogenerasi, 2025)
This study aims to determine the practicality. This study is a research and development method (Research & Development) with the Plomp 2013 model consisting of three stages, namely the preliminary research phase, the prototyping phase and the assessment phase. The results of the study showed that: The learning implementation test obtained a score of 100% in the very good category, the student response obtained a score of 94.7% in the very good category, and the teacher response obtained a score of 93.8% in the practical category. Development of Story Book-based Teaching Materials about Ecosystems in Developing the Character of Pancasila Student Profiles at SMA Negeri 2 Tilamuta which has been developed and has met the criteria of being very feasible and practical.